Barriers to adequate pain and symptom relief at the end of life: A qualitative study capturing nurses' perspectives. Issue 1 (February 2022) - Gerber, Katrin; Willmott, Lindy; White, Ben; Yates, Patsy; Mitchell, Geoffrey; Currow, David C.; Piper, Donella
Abstract: Background: Symptom management remains a critical challenge at the end of life. Barriers to symptom relief predominantly focus on perspectives of physicians, patients or care systems but rarely acknowledge the views of nurses. Aim: Examine nurses' perceptions of barriers to adequate end-of-life symptom relief. Methods: Semi-structured interviews with 25 nurses across different settings who routinely prescribed and/or administered symptom relief to patients near the end of life in Queensland and New South Wales, Australia. Data were analysed using a six-stage hybrid thematic analysis technique. Findings: Nurses identified five barriers to adequate symptom management. Firstly, fears concerning symptom relief such as hastening death, causing addiction, loss of consciousness, and legal/professional repercussions affected clinical practice. Secondly, lack of knowledge, experience and training hindered symptom management. Nurses discussed knowledge gaps regarding medication and palliative care, symptom assessments, recognition of dying and relevant laws. Thirdly, personal, cultural and religious beliefs influenced staff's willingness to offer pain relief, and patients' and families' willingness to accept it. Lack of communication between medical teams, patients and families further challenged symptom management. Lastly, institutional barriers played a considerable role as time constraints, insufficient staff support and difficulties accessing resources prevented end-of-life symptom management. Discussion: The identified barriers highlight a substantial need for targeted interventions. Setting-specific challenges such as limited access to medication, staff and palliative care services must be addressed. Conclusions: To provide better end-of-life care, services should acknowledge nurses' unique insights. Particular attention should be on supporting nurses in aged care facilities, community settings and remote areas.